Macroeconomic Aspects of Investment Activity of Banks - Mammedov, E.Ch. (Управління економікою: теорія та практика, 2022)
Bank investments have a special economic content. In the microeconomic aspect, the investment activity of the bank can be viewed from the point of view of the bank taken as an economic subject (as an activity in which the bank acts as an investor by putting its resources into the creation or acquisition of real assets, and the purchase of financial assets with the aim of generating direct and indirect income). However, there is another aspect of banks' investment activities that is related to the implementation of their macroeconomic role. In this capacity, banks cause the realization of the investment demand of economic entities in the form of money and credit in the market economy, and the transformation of savings and savings into investment. Therefore, in the macroeconomic aspect, the investment activity of banks is understood as an activity aimed at meeting the investment needs of the economy.